Facet Control for Trap‐State Suppression in Colloidal Quantum Dot Solids. (6th April 2020) - Xia, Yong; Chen, Wei; Zhang, Peng; Liu, Sisi; Wang, Kang; Yang, Xiaokun; Tang, Haodong; Lian, Linyuan; He, Jungang; Liu, Xinxing; Liang, Guijie; Tan, Manlin; et al.
Abstract: Trap states in colloidal quantum dot (QD) solids significantly affect the performance of QD solar cells, because they limit the open‐circuit voltage and short circuit current. The 100 facets of PbS QDs are important origins of trap states due to their weak or missing passivation. However, previous investigations focused on synthesis, ligand exchange, or passivation approaches and ignored the control of 100 facets for a given dot size. Herein, trap states are suppressed from the source via facet control of PbS QDs. The 100 facets of ≈3 nm PbS QDs are minimized by tuning the balance between the growth kinetics and thermodynamics in the synthesis. The PbS QDs synthesized at a relatively low temperature with a high oversaturation follow a kinetics‐dominated growth, producing nearly octahedral nanoparticles terminated mostly by 111 facets. In contrast, the PbS QDs synthesized at a relatively high temperature follow a thermodynamics‐dominated growth. Thus, a spherical shape is preferred, producing truncated octahedral nanoparticles with more 100 facets. Compared to PbS QDs from thermodynamics‐dominated growth, the PbS QDs with less 100 facets show fewer trap states in the QD solids, leading to a better photovoltaic device performance with a power conversion efficiency of 11.5%. Abstract : The 100 facets of ≈3 nm PbS quantum dots (QDs) are minimized by tuning the balance between the growth kinetics and thermodynamics in the synthesis. Compared to PbS QDs from thermodynamics‐dominated growth, the PbS QDs with less 100 facets show fewer trap states in the QD solids, leading to a better photovoltaic device performance with a power conversion efficiency of 11.5%.